Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology - Jorge, Gabrielle; Libonatti, María Laura; Benetti, Cesar João; Hamada, Neusa (Zootaxa, 2019)
In this paper we describe and illustrate for the first time the immature forms (larva and pupa) of Ora semibrunnea Pic, 1922, including biological information and behavior observed in the laboratory. This is the first record of the occurrence of this species in the Brazilian Amazon region. Larvae and pupae were found in natural lakes associated with macrophyte banks. Pupae are aquatic and have morphological adaptations (well-developed pronotal siphons) to obtain atmospheric O2 at the water surface.